If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 12 = 2x + 4 Reorder the terms: 12 + -2x = 2x + 4 Reorder the terms: 12 + -2x = 4 + 2x Solving 12 + -2x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + -2x + -2x = 4 + 2x + -2x Combine like terms: -2x + -2x = -4x 12 + -4x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + -4x = 4 + 0 12 + -4x = 4 Add '-12' to each side of the equation. 12 + -12 + -4x = 4 + -12 Combine like terms: 12 + -12 = 0 0 + -4x = 4 + -12 -4x = 4 + -12 Combine like terms: 4 + -12 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| 13.2-3.9= | | 4m-m+16=9m+(-30) | | 4y+28y^2=0 | | 4t+2+t=57 | | 3(4x+5)-2=6x+1 | | 3947.2833=1/3*342.25*h | | 87-x=97 | | c/3-3=10 | | 9y+y+3y= | | 18-2x=-60-15x | | 28.4+46.9a=75.3 | | y=Ix+2I-4 | | X-6.8=9.4 | | 9h^2-36h=0 | | 7x-3+34=180 | | 10x+3=10+9x | | cos(68)=4/x | | Z-8.4=-3.3 | | -3x+-5x-7=-12 | | 75+2t=t-6 | | 7(x+1+y)=14x | | 3(t+2)1=8 | | U/4-9=15 | | 0.37/5.18 | | R-9.5=-7.1 | | 10x+4=60x+2 | | A-3.3=4.9 | | 5q^2-7=0 | | X^2+y^2-18x+20y+180=0 | | 7(-3r+4)=91 | | (16x^(4)y^(12))^((3)/(4)) | | (xy)(x^3-2xy+4y^2)= |